A unified framework for thai metadata extraction using case-based reasoning - Krisda Khankasikam (2018)
Metadata is a very popular word in information technology today because it helps users to differentiate significant documents from non-significant documents. With the growth of the Internet and related tools, there has been a rapid growth of online resources. However, lack of metadata available for these resources stops their discovery and dissemination over the Internet. The process for manual metadata extraction is time-consuming, costly, and labor-extensive. This paper describes a framework for automatic metadata extraction from electronic Thai documents. The system consists of three main components: a case retrieval module for comparing problem case and stored case using nearest neighbor retrieval technique, a metadata creation module for automatically extracting metadata from electronic Thai documents using Thai information extraction techniques, and a metadata verification module for correcting the errors in extracted metadata. The experimental results show that using the proposed framework could reduce the labor work of Thai metadata creation process. © 2008 IEEE.